United Kingdom-European Union Relations in the post Brexit Era- Northern Ireland Protocol - Omar Manfi Adday; Dr. Ogr Uyesi Oguz Guner (Scholar Express Journals, 2023)
United Kingdom-European Union Relations in the post Brexit Era- Northern Ireland Protocol
Keywords: Brexit